Long-Term Effects of Hiring Subsidies for Low-Educated Unemployed Youths - Andrea Albanese; Bart Cockx; Muriel Dejemeppe (Institute of Labor Economics (IZA), 2023)
We use a regression discontinuity design and difference-in-differences estimators to estimate the impact of a one-shot hiring subsidy for low-educated unemployed youths during the Great Recession recovery in Belgium. The subsidy increases job-finding in the private sector by 10 percentage points within one year of unemployment. Six years later, high school graduates accumulated 2.8 quarters more private employment. However, they substitute private for public and self-employment; thus, overall employment does not increase but is still better paid. For high school dropouts, no persistent gains emerge. Moreover, the neighboring employment hub of Luxembourg induces a complete deadweight loss near the border.
Keywords: C21; J08; J23; J24; J64; J68; J61; 330; hiring subsidies; youth unemployment; low-educated; regression discontinuity design; difference-in-differences; spillover effects